PENERAPAN PERMAINAN TREASURE HUNTING UNTUK MENGEMBANGKAN KEMAMPUAN MENGENAL BENTUK BANGUN RUANG DI SD NEGERI PANTE CERMIN - Uci Mahlisa; Riska Ariani (LPPM Universitas Cipta Mandiri, 2026)
Treasure hunting is a game of searching for an object hidden in a certain place using the help of several clues. Based on initial observations of first-grade students of Pante Cermin Elementary School, researchers found that some students were still unfamiliar with geometric shapes. This was due to the lack of learning media regarding geometric shapes used by teachers during the learning process. The aim of this study was to determine the effect of treasure hunting games on the ability to recognize geometric shapes in grade 1 students of Pante Cermin State Elementary School. The research method used was a quasi-experimental with a pretest-posttest control group design. The results showed the results of the pretest data with a total score of 54.164% with the criteria of Developing According to Expectations (BSH). However, during the posttest after being given treatment through the treasure hunting game, the total score increased by 90.413% with the assessment criteria of developing Very Well (BSB). Furthermore, the results of the hypothesis testing used the ttest where the ttable value obtained was 1.72913 while the tcount value was 1.4. So tcount < ttable so that Ho was rejected and Ha was accepted. Thus, it is proven that the treasure hunt game influences the ability to recognize geometric shapes in 6-7 year old children at Pante Cermin Elementary School.